2011
DOI: 10.1007/s00167-011-1663-1
|View full text |Cite
|
Sign up to set email alerts
|

Ligamentum teres: a functional description and potential clinical relevance

Abstract: IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
82
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(87 citation statements)
references
References 25 publications
(37 reference statements)
4
82
0
1
Order By: Relevance
“…An apprehension test with a provocative maneuver is also executed in the lateral position (Fig. 6c), including a forward force to test antero-inferior instability [22]. Beyond the capsular and teres ligament, this test is also useful to detect acetabular antero-inferior hypoplasia.…”
Section: Lateral Examinationmentioning
confidence: 99%
“…An apprehension test with a provocative maneuver is also executed in the lateral position (Fig. 6c), including a forward force to test antero-inferior instability [22]. Beyond the capsular and teres ligament, this test is also useful to detect acetabular antero-inferior hypoplasia.…”
Section: Lateral Examinationmentioning
confidence: 99%
“…Studies have also examined the properties of the ligamentous structures of the hip point. Myers et al [29] found the iliofemoral ligament served as a primary stabilizer for limiting external rotation and preventing anterior translation of the femoral head Martin et al [30] conducted a retrospective study of 350 surgical patients that 20 patients identified with complete ligamentum teres rupture. A string model was used to determine the ligament excursion of these subjects.…”
Section: Layer Ii: Inert Layermentioning
confidence: 99%
“…The effect of LT on hip stability in dysplastic hips and hyperlaxity has been emphasized before [4][5][6]. In their study Martin et al reported that patients with resected LT had feelings of instability and discomfort [5]. The prevalance of LT tears detected at hip arthroscopy varies between 4% and 15% [7] .…”
Section: Introductionmentioning
confidence: 99%